Parallel algorithms for a multi-level network optimization problem - Cruz, F.R.B.; Mateus†, G.R. (Parallel algorithms and applications, 2003)
Multi-level network optimization (MLNO) problems arise in many contexts such as telecommunication, transportation, or electric power systems. This paper is mainly concerned with parallel implementations of the classical branch-and-bound algorithm for multi-level network design. A model for such a problem is presented and formulated as a mixed-integer program. The formulation is appealing because it integrates in the same model aspects of discrete facility location, topological network design, and dimensioning. We propose implementations that are suitable for multiple instruction stream, multiple data stream (MIMD) parallel computation systems. Thus, the implementations are very convenient for use in networks of workstations, which nowadays has become so popular. We have tested two versions of the branch-and-bound algorithm as well as different load balancing strategies. The results are very encouraging indicating a gain over sequential computations in terms of execution time.